2003
DOI: 10.1063/1.1531622
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the vibrational exciton approach for CO2 and N2O nanoparticles

Abstract: It is investigated how far the vibrational exciton approximation is suitable to describe the characteristic band shapes in the infrared spectra of CO2 and N2O nanoparticles. The particles typically contain between 50 and 104 molecules and have spatial dimensions between 1 and 10 nm. The accuracy of the exciton approach is estimated by comparison with experimental data and quantum chemical calculations for small clusters. The spectral changes due to different particle shapes and particle sizes are investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 51 publications
4
97
0
Order By: Relevance
“…This effect has its molecular origin in strong transition dipole coupling (vibrational exciton coupling). 35,38,39 As we have discussed and verified by modeling in previous publications, 34, 36 the time evolution of these bands is the result of a shape change from cube-like particles to particles with increasingly elongated shapes. The ν 3 band of the cube-like particles features a strong central peak (2361.0 cm −1 ) with a weak, higher energy side peak (2371.2 cm −1 ).…”
Section: A Pure Co 2 and Pure C 2 H 2 Aerosolsmentioning
confidence: 67%
“…This effect has its molecular origin in strong transition dipole coupling (vibrational exciton coupling). 35,38,39 As we have discussed and verified by modeling in previous publications, 34, 36 the time evolution of these bands is the result of a shape change from cube-like particles to particles with increasingly elongated shapes. The ν 3 band of the cube-like particles features a strong central peak (2361.0 cm −1 ) with a weak, higher energy side peak (2371.2 cm −1 ).…”
Section: A Pure Co 2 and Pure C 2 H 2 Aerosolsmentioning
confidence: 67%
“…They are called LO modes, and they always appear at higher frequencies than the TO modes. The theory describing the properties of these surface or longitudinal modes, and the spectral features that can appear between the LO and TO frequencies, have been extensively described in the literature (27,(32)(33)(34)(35)(36). The magnitude of the LO-TO separation is given by…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, it is a quantum mechanical model to calculate the IR extinction spectra for molecular nanoparticles. It has been previously shown that for vibrations with a transition dipole moment greater than 0.1 D, the dominant contribution to the IR band shape is resonant dipole coupling (exciton coupling) [1,[34][35][36][37][38][39][40][41][42][43][44][45]. This coupling lifts the degeneracy of the uncoupled molecular vibrational states and leads to vibrational eigenfunctions that are delocalised over the particle.…”
Section: Vibrational Exciton Calculationsmentioning
confidence: 99%
“…A detailed description of this model can be found elsewhere [1,[34][35][36][37]. Briefly, it is a quantum mechanical model to calculate the IR extinction spectra for molecular nanoparticles.…”
Section: Vibrational Exciton Calculationsmentioning
confidence: 99%